Assessment of the Main Economic Indicators of Tourism Development in Kazakhstan - ALTAIBAYEVA, Zhanat K.; KHAMZINA, Sholpan S.; BAUER, Maira S.; MUTALLYAPOVA, Shynar E.; NARYNBAYEVA, Aina S.; ALIMKHANOVA, Roza K. (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
Population growth and growth in its material welfare are important factors for changing the needs for recreation, making recreation a dynamic element. In this article, the authors consider the results of their analytical study of economic aspects of the development of tourism in Kazakhstan. In particular, the indicators of direct tourism, the dynamics of domestic and inbound tourist flow over a number of years in a regional context are analysed. Common weaknesses and potential for development of the industry are noted. The type of tourist services consumer is described by education, mobility, individualism and independence, awareness, greening of consciousness, insistence on high standards of services. The results of the study allowed the authors to draw a number of interesting conclusions that allow us to assess the overall state and importance of the industry for the country's economy, consumer activity in the tourist services market.